2017
DOI: 10.3126/cs.v4i1.16891
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Human-Wildlife Conflict and People’s Perception towards Compensation Program in Nilambur, Southern Western Ghats, India

Abstract: SummaryAim The aim of this research was to examine patterns of human-wildlife conflict and assess community perception towards compensation program implemented to ameliorate human-wildlife co-existence.Location North and South Forest Divisions, Nilambur, South India. Material and Methods Key findingsCrop damage was the most common type of conflict, followed by property damage, injury and death by wildlife attack. Crop damage was contributed mainly by elephant (Elephas maximus) (59%) and wild boar (Sus scrofa)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Similarly, a study from South India reported that crop damage was the most common type of conflict, followed by property damage, injury and death by wildlife attack. Crop damage was contributed mainly by elephant (Elephas maximus) (59%) and wild boar (Sus scrofa) (32%) in South India [25].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study from South India reported that crop damage was the most common type of conflict, followed by property damage, injury and death by wildlife attack. Crop damage was contributed mainly by elephant (Elephas maximus) (59%) and wild boar (Sus scrofa) (32%) in South India [25].…”
Section: Discussionmentioning
confidence: 99%
“…The 81% responded that wildlife should be conserved, while 19 % were not interested in wildlife conservation. Comparable results were obtained by Rohini et al (2016) when the attitude towards elephants in the southern western ghats of Kerala was analyzed. Perceptions of people about the lack of proper compensation and long-term procedures for the same from the forest department were close to previous studies (Gubbi 2012, Karanth et al 2013).…”
Section: Attitude Toward the Conservation Of Wildlifementioning
confidence: 77%
“…Substantial populations of bonnet macaques thrive in regions of Kerala adjoining wildlife habitat. They are generally viewed as pests and forest department officials often deal with complaints from the public when macaques steal food from local homes or restaurants, damage property or display aggression (Rohini et al 2016). Incidents of deliberate poisoning of macaques are thus not uncommon (Ragothaman and Chirukandoth 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Wild boars frequently cause extensive agricultural losses in Kerala (Rohini et al 2016) and retaliatory poisoning is commonly reported (Kalaivanan et al 2011). They also scavenge food waste from garbage dumps close to human habitation, posing a potential risk to people.…”
Section: Resultsmentioning
confidence: 99%